From Fragmentation to Coherence: Enhancing Human Resource Capacity in Indonesian Law Reform for Effective Justice Delivery - Odi Jarodi; Muhammad Khafid; Arief Yulianto (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
Indonesian law reform faces persistent challenges stemming from fragmented human resource capacity, which undermines the coherence and effectiveness of justice delivery. This study critically examines the interplay between human resource development and the success of legal reform in Indonesia, emphasizing the urgent need to address systemic inefficiencies and skill gaps. As globalization and complex socio-legal issues demand more sophisticated legal systems, the pressure on Indonesia’s legal institutions to enhance their human resource capabilities has intensified. The novelty of this research lies in its focused analysis of human resource capacity as a critical yet underexplored dimension of Indonesian law reform. By employing a socio-legal methodology, the study identifies key factors contributing to fragmentation, including uneven competency levels, inadequate training, and lack of coordination among legal institutions. It further evaluates the role of education, professional development, and policy frameworks in fostering a coherent and competent legal workforce. The findings demonstrate that a robust, well-coordinated human resource strategy is essential for advancing legal reforms and delivering justice effectively. This research contributes to the discourse by proposing actionable solutions, including curriculum reforms, capacity-building initiatives, and collaborative networks among legal practitioners, academics, and policymakers. By addressing the critical gap in human resource capacity, this study provides a pathway for achieving a coherent legal system that upholds justice and aligns with Indonesia’s broader development goals.